حجاجية الاستعارة عند "عبد القاهر الجرجاني - عبد السلام عابي; سالم محمد يزيد (Université de M'sila, 2018)
يعدُّ " عبد القاهر الجرجاني " رائد علوم البلاغة العربية ،و عن طريقه تبلورت النظرة الدقيقة لمختلف مفاهيم البلاغة ،و من أبرز هذه المفاهيم مفهوم الاستعارة الذي ذهب فيه مذهبا سابقا لأوانه متجاوزا عصره ، إذ يعدُّ أول من تفطن إلى الوظيفة الحجاجية للاستعارة ،فقد تناول الاستعارة في إطار نظرية النظم التي ملكت عليه لبه ، و التي يحتج من خلالها على فصل المعنى على اللفظ ،و يجعل الاستعارة من المعاني و ليس من الألفاظ؛أي في إطار نظمها و سياقها، ليتحقق فيها ما تطويه من سعة التصوير و رحابته.و قد اعتبر الجرجاني حجاجية الاستعارة قائمة على مفهوم" الادعاء"،وهذا ما سنقف عليه في هذا البحث. Abstract: Abdul Qahir Al-Jarjani is the pioneer of the Arabic dialectic sciences, and through it crystallized the accurate view of the various concepts of rhetoric. The most prominent of these concepts is the concept of metaphor in which he went a doctrine prematurely beyond his age. He is the first to grasp the function of pilgrimage to metaphor. In the context of the theory of the systems which he has acquired, and in which he invokes the separation of the meaning of the word, and makes the metaphor of the meanings and not of the words; that is, within the framework of their systems and context, to achieve what is increasing the capacity of photography and its welcome. Al-JarjaniHajjaj metaphor is based on the concept of "prosecution", and this is what We stand.
Keywords: metaphors; pilgrims; rhetoric; allegation; context; heritage